PENGETAHUAN ANGGOTA DEWAN TENTANG ANGGARAN, AKUNTABILITAS PUBLIK, TRANSPARANSI KEBIJAKAN PUBLIK DAN PENGAWASAN KEUANGAN DAERAH - Fahmi Poernamawatie; Ronny Hendra (Universitas Gajayana Malang, 2017)
Regional Government as an Executive has a duty to prepare Government Budget (APBD), on the other hand, Regional House of Representatives (DPRD) has the right to control the raising and spending of public money that disclosure on APBD. This research investigates the impact of knowledge about budgets, understanding on public accountability, and transparency of public policy either partially or simultaneously to Regional Government Budget (APBD) using data from 120 members of Regional House of Representatives in Malang Raya. Three hypotheses were formulated for the study and tested using F-test and t-statistic. The study relied on primary data from 120 members of DPRD in Malang Raya. The results of this study prove that: 1) Knowledge of DPRD about the budget, public accountability, and transparency of public policy, it is generally inadequate; 2) Knowledge of the DPRD about the budget, public accountability, and transparency of public policy either simultaneously or partially significant effect on controlling to Regional Government Budget (APBD) and have a positive significant relationship. Furthermore, the variable most dominant influence on the supervision of the budget is the knowledge about the budget.